Strategies for Controlling Dye Liquid Waste Pollution in Sasirangan Village, Sungai Jingah Village, Banjarmasin City - Rusmawati, Devi; Adyatma, Sidharta; Aristin, Nevy Farista (JPG (Jurnal Pendidikan Geografi), 2024)
Water pollution increases every year even though water has an indispensable role for every human activity and other living things. Pollution is caused by chemicals or other substances. Consequences of irresponsible environmental management Poor environmental management can lead to a decrease in available water supplies. The function of the river is very important for the community in Banjarmasin City so that it is vulnerable to pollution because most community activities are carried out in the river, be it household activities, industry, domestic, agriculture, mining, and the like. This study aims to analyze the control strategy of colored liquid waste pollution in Sasirangan Village, Sungai Jingah Village, Banjarmasin City. The variables in this study are related to the control of internal and external pollution factors. Determine the sample using non probability sampling, namely purposeful sampling. The data types used are primary data and secondary data. Primary data was collected through field observations and distribution of questionnaire. Secondary data were obtained from institutions, literature studies and document studies. The type of research used by researchers is quantitative descriptive research. The data processing technique used consists of: editing, coding, scoring, and tabulating then analyzed using SWOT. From the results of tabulating and SWOT analysis in the Grand Strategy Matrix, it can be seen that the most appropriate strategy is in the position of Devensif Strategy (Defense Strategy).